Kehadiran Berkontribusi dalam Peningkatan Kinerja Akademik Mahasiswa - Hanifa, Silvia; Khusaini, Khusaini; Widiarti, Aniek (SAP (Susunan Artikel Pendidikan), 2024)
Academic performance is an important indicator of the final results of teaching and learning activities. Attendance as a determinant of academics is still a matter of debate. This research aims to examine student attendance in class on student performance at FKIP UNIS Tangerang for the 2022/2023 Academic Year. Researchers utilized a sample size of 216 which were obtained simply at random (Slovin, sampling error 1%). Data collection used an online questionnaire which had been validated and distributed using the WhatsApp application. The estimation results using multiple regression analysis showed that student attendance in class contributed significantly to determining academic performance, while self-efficacy and previous academic abilities had not been proven to be determinants of academic performance. This finding implies that students maintain an attendance rate of at least 75% so that their academic performance is better. Monitoring student attendance can be used as an instrument to maintain the quality of higher education.